Effect of Prenatal Yoga On Back Pain and Sleep Quality in Pregnant Women: A Scoping Review - Heriyanti, Silvia Widyani; Adnani, Qorinah Estiningtyas Sakilah; Rohmah, Siti; Fatimah, Siti (Poltekkes Kemenkes Palu, 2024)
Throughout pregnancy, the expectant mother experiences physiological and psychological alterations. These modifications can significantly affect the mother's many pregnancy complications, including respiratory difficulties, lumbar discomfort, haemorrhoids, and sleep disruptions. Background: Lower back pain (LBP) is a musculoskeletal ailment that can negatively impact the overall well-being of pregnant women. Failure to promptly address the complaint might have detrimental effects on both the mother and the fetus. Objective: This scoping review seeks to examine the effects of prenatal yoga on the occurrence of back pain and the quality of sleep in pregnant women. Methods: This article conducted a scoping review using the PRISMA approach. Articles published in the last five years (2019-2023) were identified through various sources, including Google Scholar, PubMed, Journal SAGE, Scopus, Science Direct, and EBSCO. This search yielded ten relevant journals. Findings: Our examination revealed that engaging in prenatal yoga during pregnancy can help pregnant women reduce back pain and improve the quality of their sleep. Conclusion: prenatal yoga is a non-pharmacological therapeutic option for pregnant women to alleviate back discomfort and enhance sleep quality.